Журнали про спорт – як зацікавити підлітків - Сокольцов, В. (My University, 2020)
In this paper, we study the issue of publishing popular and scientific periodicals on sports in Ukraine, as well as the publication of sports publications for teenagers. We consider a periodical that talks about the new Workout direction and the people who are developing this sports direction in Kharkov
Keywords: періодичні видання; спортивні журнали; підлітки